Multimodal Evoked Potentials as Potential Biomarkers of Disease Activity in Patients With Clinically Isolated Syndrome - Dziadkowiak, Edyta; Wieczorek, Małgorzata; Zagrajek, Mieszko; Chojdak-Łukasiewicz, Justyna; Gruszka, Ewa; Budrewicz, Sławomir; Pokryszko-Dragan, Anna (Frontiers in Neurology, 2022)
Objective: The goals of the study were: to conduct a 3-year longitudinal evaluation into multimodal evoked potentials (EP) and cognition in patients with clinically isolated syndrome (CIS), and to assess the prognostic value of baseline electrophysiological and neuropsychological findings with regard to the disease outcomes. Methods: In 29 patients (20 women, 9 men, mean age 31.1) multimodal (visual, brainstem auditory, somatosensory, event-related) EP and neuropsychological tests (NT) were performed at baseline, after 1 (T1) and 3 (T3) years. Their results were compared longitudinally between baseline, T1 and T3. Baseline results were referred to conversion of CIS into multiple sclerosis (MS) and disability level during the follow-up. Results: Apart from mean N13/P16 SSEP amplitude (lower at T1 and T3 than at baseline (T1 1.02μV, T2 0.88μV, T3 0.75μV p < 0.05), no significant changes of EP or NT parameters were found in longitudinal assessment. Baseline P300 latency was longer for the patients with MS than for those with CIS at T1 (345.50ms vs. 325.75ms).The patients classified as MS at T3, in comparison with those with CIS, had at baseline longer latency of III and V (3.99ms vs. 3.75ms and 5.96ms vs. 5.67), prolonged interlatency I-III (2.3ms vs. 2.05ms) and I-V (4.23ms vs. 3.94ms) and reduced amplitude of V (0.28μV vs.0.42μV) components of BAEP. Significance: Abnormal parameters of BAEP and ERP revealed subclinical neurological deficit in the patients with CIS and predicted their early conversion into MS. ERP, as a marker of cognitive performance, are worth considering in multimodal EP evaluation at early stage of MS.